Screening of butternut (Cucurbita moschata) cultivars for resistance to Black rot caused by Stagonosporopsis spp. - Coutinho, Teresa A. (University of Pretoria, 2023)
Dissertation (MSc (Agric) Plant Pathology))--University of Pretoria, 2022.